South‐East Asia study alliance guidelines on the management of acne vulgaris in South‐East Asian patients. Issue 10 (25th July 2015) - Goh, Chee Leok; Abad‐Casintahan, Flordeliz; Aw, Derrick Chen Wee; Baba, Roshidah; Chan, Lee Chin; Hung, Nguyen Thanh; Kulthanan, Kanokvalai; Leong, Hoe Nam; Medina‐Oblepias, Marie Socouer; Noppakun, Nopadon; Sitohang, Irma Bernadette; Sugito, Titi Lestari; et al.
Abstract The management of acne in South‐East Asia is unique, as Asian skin and local variables require a clinical approach unlike that utilized in other parts of the world. There are different treatment guidelines per country in the region, and a group of leading dermatologists from these countries convened to review these guidelines, discuss current practices and recent advances, and formulate consensus guidelines to harmonize the management of acne vulgaris in the region. Emphasis has been placed on formulating recommendations to impede the development of antibiotic resistance in Propionibacterium acnes. The group adopted the Acne Consensus Conference system for grading acne severity. The group recommends that patients may be treated with topical medications including retinoids, benzoyl peroxide (BPO), salicylic acid, a combination of retinoid and BPO, or a combination of retinoids and BPO with or without antibiotics for mild acne; topical retinoid with topical BPO and a oral antibiotic for moderate acne; and oral isotretinoin if the patient fails first‐line treatment (a 6‐ or 8‐week trial of combined oral antibiotics and topical retinoids with BPO) for severe acne. Maintenance acne treatment using topical retinoids with or without BPO is recommended. To prevent the development of antibiotic resistance, topical antibiotics should not be used as monotherapy or used simultaneously with oral antibiotics. Skin care, comprised of cleansing, moisturizing and sun protection, is likewise recommended. Patient education and good communication is recommended to improve adherence, and advice should be given about the characteristics of the skin care products patients should use.